Search for quasiparticle scattering in the quark-gluon plasma with jet splittings in pp and Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Menzel, Marius; Nath, Abhishek; et al. (Physical review letters, 2025)
The ALICE Collaboration reports measurements of the large relative transverse momentum (𝑘𝑇) component of jet substructure in 𝑝⁢𝑝 and Pb-Pb collisions at center-of-mass energy per nucleon pair √𝑠NN=5.02 TeV. Enhancement in the yield of such large-𝑘T emissions in head-on Pb-Pb collisions is predicted to arise from partonic scattering with quasiparticles of the quark-gluon plasma. The analysis utilizes charged-particle jets reconstructed by the anti-𝑘T algorithm with resolution parameter 𝑅 =0.2 in the transverse-momentum interval 60<𝑝T,ch,jet<80 GeV/𝑐. The soft drop and dynamical grooming algorithms are used to identify high transverse momentum splittings in the jet shower. Comparison of measurements in Pb-Pb and 𝑝⁢𝑝 collisions shows medium-induced narrowing, corresponding to yield suppression of high-𝑘𝑇 splittings, in contrast to the expectation of yield enhancement due to quasiparticle scattering. The measurements are compared to theoretical model calculations incorporating jet modification due to jet-medium interactions (“jet quenching”), both with and without quasiparticle scattering effects. These measurements provide new insight into the underlying mechanisms and theoretical modeling of jet quenching.